Social engagement and subjective health among older adults in South Korea: Evidence from the Korean Longitudinal Study of Aging (2006-2018) - Bo Zhao; Ji Eon Kim; Jiyoung Moon; Eun Woo Nam (Elsevier, 2023)
Background: Social engagement serves as the foundation for social connections by providing a sense of belonging, social identity, and fulfillment. Previous studies have mainly focused on the one-way relationship between social engagement and subjective health among older individuals, and little attention has been paid to their mutual relationship. Therefore, this study aimed to examine the mutual association relationship between social engagement and their subjective health in older Koreans. Methods: Seven waves of data samples (aged ≥60 years) from 2006 to 2018 from the Korean Longitudinal Study of Aging (KLoSA) was used in this study. Descriptive analysis, chi-squared tests, 2-year lagged Generalized estimating equation (GEE) model, and cross-lagged panel model were performed to investigate the mutual association between social engagement and subjective health among six survey periods. Results: Results of the GEE model revealed when controlling for other variables, older Koreans who reported good subjective health only had a higher OR (1.678 vs. 1.650, p < 0.001) of participating in social engagement than those who had bad subjective health in 2006-2008 period; the occurrence rate of more social engagement was significantly higher among older adults with good subjective health than among those with bad subjective health (five out six survey periods). Cross-lagged analysis showed similar results that coefficients of social engagement on subjective were relatively larger in three survey periods; coefficients of subjective health on social engagement were relatively larger in the other three survey periods. The impact of social engagement on subjective health might be greater than that of subjective health on social engagement. Conclusion: All-around participation and engagement of older people in society have become a consensus among the international community. In view of the single social engagement activities and less relevant participation channels in Korea, government departments should consider not only regional but also local characteristics to create more social participation opportunities for older individuals.